2018
DOI: 10.2141/jpsa.0170044
|View full text |Cite
|
Sign up to set email alerts
|

Growth Performance and Right Ventricular Hypertrophy Responses of Broiler Chickens to Guanidinoacetic Acid Supplementation under Hypobaric Hypoxia

Abstract: Guanidinoacetic acid (GAA) has been shown to spare arginine (ARG) requirements in chickens. ARG plays a critical role in enhancing growth and preventing right ventricular hypertrophy (RVH) in broiler chickens subjected to hypobaric hypoxia. However, ARG is not available as a feed grade supplement in the market. Therefore, we evaluated the effects of commercially available GAA supplement as an alternative on growth performance and RVH in broilers raised at high altitude (2100 m). Five graded levels of GAA rangi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 23 publications
(32 reference statements)
2
21
0
Order By: Relevance
“…It is worth noting that adding GAA beyond 1.5 g/kg reduced the growth performance of broilers so that the difference between 1.5 and 2.25 g/kg GAA groups was significant. This observation was in agreement with the finding of Ahmadipour, Zafari Naeini, et al (), who reported a curvilinear response to GAA. These authors, however, made no explanation on how high doses of GAA could reduce the growth performance.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…It is worth noting that adding GAA beyond 1.5 g/kg reduced the growth performance of broilers so that the difference between 1.5 and 2.25 g/kg GAA groups was significant. This observation was in agreement with the finding of Ahmadipour, Zafari Naeini, et al (), who reported a curvilinear response to GAA. These authors, however, made no explanation on how high doses of GAA could reduce the growth performance.…”
Section: Discussionsupporting
confidence: 93%
“…An improvement in body weight gain and FCR by dietary GAA when supplemented at 1.5 g/kg was in line with Ahmadipour, Zafari Naeini, et al (). Growth efficiency improvements may account for regulating the phosphocreatine/creatine kinase (PCr‐CK) system by GAA.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…One‐day‐old chicks were then allocated to pens (10 birds per pen with weighted 48.5 g on average) so that all pens had equal initial body weights (485 ± 10 g). The house temperature was set at 32 ± 1°C during Week 1, 25 ± 1°C for Week 2, 20 ± 1°C for Week 3 and 15 ± 1°C until the end of trial (42 days of age) as previously described (Ahmadipour et al, ). Birds were subjected to 23‐hr light and 1‐hr dark throughout the trial.…”
Section: Methodsmentioning
confidence: 99%
“…Factors that dilate the pulmonary vasculature and thereby lower the resistance (vasodilation) to blood flow can delay or inhibit the onset of pulmonary hypertension. Neurotransmitter acetylcholine (Ach; Odom et al, ), eicosanoids prostaglandin I2 (PGI 2 ), prostaglandin E 2 (PGE 2 ; Stebel & Wideman, ), adrenomedullin (AM; Gomez, Moreno, Iglesias, Coral, & Hernandez, ), nitric oxide (NO; Ahmadipour, Zafari Naeini, Sharifi, & Khajali, ) and phenolic flavonoids compounds (Ahmadipour, Hassanpour, Asadi, et al, ). In broilers, ET‐1 elicits dose‐dependent constriction of pulmonary arteries that can be modulated by nitric oxide (Odom et al, ).…”
Section: Introductionmentioning
confidence: 99%